INTEGRATING LOCAL WISDOM IN ISLAMIC RELIGIOUS EDUCATION: SHAPING RELIGIOUS AND CULTURAL IDENTITY AT SMPIT BINTANG TANGERANG - Nurdin, Nurdin; Jamila, Siti (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study aims to analyze the integration of local wisdom values in Islamic religious education and its impact on the formation of students' religious and cultural identities at SMPIT Bintang Kota Tangerang. Method: Using a qualitative approach with a case study design, this study collected data through in-depth interviews with three key informants: an Islamic religious education teacher, the principal, and a student. Result: The findings show that SMPIT Bintang has systematically implemented the integration of local wisdom through community-based project learning, local case studies, community leader involvement, and the use of cultural artifacts. This integration resulted in a significant increase in students' cognitive understanding of Islamic values, the development of positive affective attitudes towards local cultural heritage, and behaviors that reflect the values of moderation, tolerance, and social responsibility.Conclusion:  This learning strategy, which integrates local and universal perspectives, creates meaningful and relevant learning and is able to build strong emotional connections between students and the values being taught. However, the implementation of this approach still faces challenges related to value balance, resource limitations, and stakeholder perceptions. Implication: This study recommends the need for ongoing institutional commitment, professional teacher training, and a measurable learning evaluation system to optimize the effectiveness of integrating local wisdom into Islamic religious education.